Application of Neutron-Gamma Analysis for Determining Compost C/N Ratio. Issue 3 (3rd July 2019) - Yakubova, Galina; Kavetskiy, Aleksandr; Prior, Stephen A.; Allen Torbert, H.
Abstract: The possible application of Pulsed Fast/Thermal Neutron Analysis (PFTNA) for determining the carbon-to-nitrogen ratio (C/N) of compost will be discussed. This analysis method has several advantages over traditional chemical analysis, including that it is a nondestructive in situ method that does not require extensive sample collection and it analyzes much larger volumes of material (∼1 m 3 ) than traditional chemical analysis (∼1 cm 3 ). The amount of carbon can be determined by irradiating compost with neutrons and measuring the gamma ray peak at an energy of 4.44 MeV that appears due to inelastic scattering. Nitrogen can be determined by measuring the gamma ray peak at 10.83 MeV that appears due to thermal neutron capture. For C/N measurements, a calibration line that relates the C/N mass ratio to the carbon/nitrogen gamma peak ratio should first be constructed; our calibration line was constructed using carbon–ammonium nitrate mixtures. PFTNA measurements were then used to determine carbon and nitrogen peak values in order to utilize the calibration line for calculating the C/N mass ratio. The workability of this methodology has been demonstrated in laboratory experiments. The applicability of PFTNA for compost C/N ratio determinations was evaluated with Monte Carlo computer simulations of neutron propagation in large compost volumes (Geant4 toolkit) and experimental measurements of real compost (volume 1.3 m 3 ). Data from computer simulations and experiments demonstrated that the PFTNA method is fully applicable for determining the C/N ratio in compost material up to values of 25 and even greater.